Investigative Authority and Institutional Autonomy in Corruption Crimes: A Comparative Study between Indonesia and Hong Kong - Erlangga, Dhani; Hafrida; Rapik, Mohamad (PAMPAS: Journal of Criminal Law, 2025)
This study investigates the comparative framework of investigative authority in corruption crimes between Indonesia and Hong Kong, focusing on the Corruption Eradication Commission (KPK) and the Independent Commission Against Corruption (ICAC). The research aims to analyze the legal foundations, institutional structures, and mechanisms of investigation employed by both countries in combating corruption, and to evaluate their effectiveness, independence, and challenges. Utilizing a normative juridical method with a comparative approach, this study relies on statutory documents, academic literature, and institutional reports as primary sources. Findings reveal that the ICAC operates under a centralized structure with clear mandates and high institutional independence, supported by the common law system, which enhances its operational effectiveness and public trust. Conversely, KPK’s authority is influenced by multi-agency coordination, a civil law system, and legal amendments that have potentially weakened its investigative autonomy and reduced efficiency. This research concludes that while Indonesia has made progress in anti-corruption efforts, structural and legal complexities hinder optimal enforcement. Strengthening KPK’s institutional independence, narrowing its functions to focus on core investigations, and adopting streamlined procedures inspired by ICAC could significantly improve anti-corruption outcomes. The Hong Kong model presents valuable lessons for Indonesia in fostering a more coherent and resilient legal framework for corruption investigation. This study offers a novel contribution by linking the relationship between legal structure and institutional independence in determining the effectiveness of corruption investigations a dimension rarely emphasized in prior comparative studies. Abstrak Penelitian ini mengkaji kerangka perbandingan kewenangan penyidikan dalam tindak pidana korupsi antara Indonesia dan Hong Kong, dengan fokus pada Komisi Pemberantasan Korupsi (KPK) dan Independent Commission Against Corruption (ICAC). Tujuan utama dari penelitian ini adalah untuk menganalisis dasar hukum, struktur kelembagaan, serta mekanisme penyidikan yang diterapkan oleh kedua negara, sekaligus mengevaluasi efektivitas, independensi, serta tantangan yang dihadapi masing-masing lembaga. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perbandingan hukum, serta didasarkan pada studi pustaka terhadap peraturan perundang-undangan, literatur akademik, dan dokumen kelembagaan yang relevan. Hasil penelitian menunjukkan bahwa ICAC beroperasi secara terpusat dengan kewenangan yang jelas dan independensi kelembagaan yang tinggi, didukung oleh sistem hukum common law yang memperkuat efektivitas operasional dan kepercayaan publik. Sebaliknya, kewenangan KPK dipengaruhi oleh sistem koordinasi antar lembaga, sistem hukum civil law, serta perubahan regulasi yang cenderung melemahkan otonomi dan efisiensi penyidikan. Penelitian ini menyimpulkan bahwa Indonesia perlu memperkuat independensi kelembagaan KPK, menyederhanakan fungsinya agar lebih fokus pada penyidikan, serta mengadopsi prosedur yang lebih ringkas seperti yang diterapkan oleh ICAC. Model Hong Kong memberikan pelajaran berharga bagi Indonesia dalam membangun sistem hukum pemberantasan korupsi yang lebih tangguh dan terarah. Kebaruan penelitian ini terletak pada analisis hubungan antara struktur hukum dan tingkat independensi kelembagaan dalam efektivitas penyidikan tindak pidana korupsi, suatu dimensi yang belum banyak dikaji dalam penelitian sebelumnya.